Land Use Assessing the Past, Envisioning the Future - Carlos Loures, Luís (IntechOpen, 2019)
The intensive increase in land use change is considered both a source of richness and a serious problem to landscape sustainability. In this scenario, although land use change plays a very important role for societal development, the impact of land use changes on economic, social, and ecological functions requires special attention. The new environmental paradigms associated with globalization and progressive climate change will certainly intensify the entropy and the instability in most of the existing land-uses. In this regard, this book aims to highlight a body of knowledge related to the discussion of the opportunities and challenges associated with the development of new sustainable landscapes, considering current and future challenges related to land-use changes and planning.